Temporalization as Transcendental Aesthetics - Avant-Garde, Modern, Contemporary - Osborne, Peter (The Nordic Journal of Aesthetics, 2014)
Reflections on the relationship of aesthetics to politics tend to circle, almost compulsively, around a relatively stable set of conceptual oppositions, inherited from German philosophies of the late 18th century. This essay proposes an expansion of the theoretical terms of the debate by extending the field of transcendental aesthetics into the domain of historical temporalization. Fundamental art-historical categories may thereby be incorporated, philosophically transformed, into ‘aesthetics’ as forms of historical temporalization: avant-garde, modern, contemporary. The essay expounds two theses, in particular: 1. The historical subsumption of the temporality of the avant-garde by the temporality of the modern: the modern stands to the avant-garde as the negation of its politics by the repetition of the new –‘the new as the ever–same’; 2. the historical subsumption of the temporality of the modern by ‘the contemporary’: the contemporary stands to the modern as the negation of the dialectical logic – and hence specifically developmentalist futurity – of the new by a spatially determined, but imaginary co-presencing. One effect of this latter subsumption, it is argued, is a particular, regressive ‘repetition of the national’, at the level of cultural representation, on the terrain of the global.